Diachronic investigations of false friends - Broz, Vlatko (2007)
False friends – pairs of words in two or more languages that are similar or equivalent graphically or phonetically but different in meaning – have been an immensely popular topic in linguistics for a long time (Koessler and Derocquigny 1928, Ivir 1968, Nilsen 1977, Chamizo Domínguez and Nerlich 2002). They are known to cause difficulty for students learning a foreign language because students are likely to misidentify the words due to language interference (Breitkreuz 1973). When translating or comparing two different languages, false friends can be created in many ways, ranging from homonymy and pseudo-anglicisms to cognates and idioms (Chamizo Domínguez 2006). There are numerous English words which share the same etymology with similar words in other European languages, but have a different meaning. In English, eventually means ‘ finally’ , whereas in most other European languages (German ‘ eventuell’ , Spanish ‘ eventualmente’ , Croatian ‘ eventualno’ ), it means ‘ possibly’ . Actual does not mean ‘ aktualan’ in Croatian, ‘ aktuell’ in German or ‘ actual’ in Spanish, which would all translate as ‘ current’ or ‘ up-to-date’ , but it means ‘ real’ or ‘ existing in act or fact’ . These examples prove that a semantic change took place in a number of English words that have cognates in other European languages, namely German, Spanish and Croatian, each taken in this research as a representative of the three major linguistic branches of the Indo-European language family: the Germanic, the Romance and the Slavic. This paper will present the results of an investigation of words such as actually eventually, etiquette, fabric, billion, chef, preservative, sensible, sympathetic, biscuit in the historical corpora of the English language. All these words have retained more or less the same meaning in German, Spanish and Croatian, whereas English shows a departure from the original meaning. I will argue that these changes were triggered off because the lexis of Middle and Early Modern English is a result of a merger of the Germanic and Romance vocabularies. Consequently, the usage of words had to change if they were to survive the cases of near synonymy. The causes for the shift in meaning will be explained through the cognitive mechanisms of metonymy and metaphor and an attempt will be made at determining the period in the development of the English language when this change was under way. The research starts with the assumption that most of these changes occurred after the period of Early Modern English, as this stage of the English language development often shares a number of semantic and syntactic features which resemble other modern European languages more than Present-Day English (Lass 1999:213, 252, 256).
Projekt MZOS
ENG